The accentuation of Latvian Curonianisms - Derksen, Rick (Baltistica, 2024)
Illič-Svityč’s reconstruction of the Curonian prosodic system is based on a less than comprehensive study of Latvian Curonianisms. Pronk uncritically endorses Illič-Svityč’s conclusions in an article on Curonian accentuation which is an accumulation of hypotheses involving language contact. Purely typological considerations do not suffice to attribute the West Latvian merger of the broken and falling tones to a Curonian substrate.
Keywords: Curonian; Latvian; Žemaitian; accentology; language contact